2011
DOI: 10.1093/jjco/hyr151
|View full text |Cite
|
Sign up to set email alerts
|

Response Rates and Adverse Effects of Continuous Once-daily Sunitinib in Patients with Advanced Renal Cell Carcinoma: A Single-center Study in Turkey

Abstract: Continuous, once-daily administration of sunitinib was generally well tolerated in Turkish patients with advanced renal cell carcinoma in a daily practice setting. This study's response rates were comparable to those in previous randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 34 publications
1
0
0
1
Order By: Relevance
“…observed in earlier randomized studies 6 . The results of previous studies also demonstrated that sunitinib is widely used in the first-or second-line settings in metastatic rcc in Turkey.…”
Section: Methodssupporting
confidence: 58%
“…observed in earlier randomized studies 6 . The results of previous studies also demonstrated that sunitinib is widely used in the first-or second-line settings in metastatic rcc in Turkey.…”
Section: Methodssupporting
confidence: 58%
“…Apesar disso, este outcome aparece utilizado em inúmeros ensaios clínicos oncológicos recentes. [8][9][10] Este indicador apresenta problemas de definição, já que é calculado através de técnicas imagiológicas. No passado, uma taxa de resposta considerava-se eficaz quando detectava uma diminuição bidimensional do volume tumoral de 50% ou mais, reconfirmada às quatro semanas.…”
Section: Taxa Objectiva De Resposta Tumoral (Objective Response Rate unclassified